Pengaruh Standar Akuntansi Pemerintah, Good Governance dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan: (Pada Badan Pengelolaan Keuangan dan Asset Daerah Kota Bandung Tahun 2022) - Utami, Rachma Hida Silfa; Berliani, Kartika (Politeknik Negeri Ambon, 2024)
This study investigates how the Bandung City Regional Financial and Asset Management Agency's internal control system, Good governance practices, and government accounting standards (SAP) will affect the quality of its financial statements in 2022. The goal of the study is to comprehend a number of variables that may impact the accuracy, dependability, and legitimacy of financial statements issued by public entities in the context of local government. The quantitative method used combines secondary data from relevant documents and literature with primary data from employee interviews who are directly involved in financial report preparation. This is done through a descriptive and verification approach. The Bandung City Regional Financial and Asset Management Agency's 82 employees and State Civil Apparatus served as the research subjects for this study, which was carried out using a probability sampling technique. The results show that there is a reporting delay even though the Bandung City Regional Financial and Asset Management Agency's financial reports are of high quality. The quality of financial statements is significantly impacted by SAP and SPIP, but not significantly by Good governance. For a more comprehensive improvement, it is therefore advised to periodically develop SAP and SPIP implementation while continuing to pay attention to Good governance issues. Keywords: Government Accounting Standards, Good Governance, Internal Control System, and Financial Statement Quality.